Hongos Fitopatógenos Asociados Al Tomate (Solanum Lycopersicum L.) En La Zona Árida Del Noroeste De México: La Importancia De Su Diagnóstico - Martínez-Ruiz, Francisco Eleazar; Cervantes-Díaz, Lourdes; Aíl-Catzím, Carlos Enrique; Hernández-Montiel, Luis Guillermo; Sánchez, Carmen Lizette Del Toro; Rueda-Puente, Edgar Omar (European Scientific Journal, ESJ, 2016)
Tomato crops are among the most important vegetables cultivated worldwide, Mexico being one of the major producing countries. Large quantity of this crop is found in states belonging to the arid northwest of the country; the adaptation of these regions to vegetable production has been significant with the support of agricultural technology due to the use of protective structures for plants, such as greenhouses and shaded mesh. However, pests and diseases are a major biotic factor that significantly reduces production. There are more than 200 diseases associated with the nightshade of various etiologies. The process of identifying the cause of a disease in plants is called diagnosis. The diagnosis of plant diseases has been described as an art and a science; it requires scientific knowledge of plant pathology and related disciplines. Effective disease control requires making the best possible decisions to reduce the risk of serious production losses. Control strategies based on prevention of disease and methods that slow the spread of such diseases. Therefore, proper management of diseases affecting the tomato crop, knowledge and understanding of the diagnosis and its infectious cycle is vital and to establish effective control measures.